Theory of endogenous growth: political economy and mathematical economy (1997)
Two essential features allow us to understand recent developments in growth theory: a new conceptualization to explain its nature, that is, the return to classical political economy and the introduction of the theory of public goods, and some mathematics that allow the formalization of this new conceptualization. With the development of bothn elements, the article presents the "new" theoretical framework, the formal conditions and the mathematical techniques needed tounderstand current growth theory. This review of these new developments can serve as a point of reference to broeciet, or to question the formulations of endogenous growth theories.